THROMBOCYTOSIS AS PROGNOSTIC FACTOR FOR SURVIVAL IN PATIENTS WITH ADVANCED NON SMALL CELL LUNG CANCER TREATED WITH FIRST- LINE CHEMOTHERAPY. - Deyan Davidov (Peytchinski Publishing, 2014)
Objective: The aim of this study was to evaluate elevated platelet count as a prognostic factor for survival in patients with advanced (stage IIIB/ IV) non- small cell lung cancer (NSCLC) receiving first- line chemotherapy. Methods: From 2005 to 2009 three hundreds forty seven consecutive patients with stage IIIB or IV NSCLC, treated in Department of Medical Oncology, UMHAT "Dr Georgi Stranski" entered the study. The therapeutic regimens included intravenous administration of platinum- based doublets. Survival analysis was evaluated by Kaplan- Meier test. The influence of pretreatment thrombocytosis as prognostic factor for survival was analyzed using multivariate stepwise Cox regression analyses. Results: Elevated platelet counts were found in 78 patients. The overall survival for patients without elevated platelet counts was 9,6 months versus 6,9 months for these with thrombocytosis. In multivariate analysis as independent poor prognostic factors were identified: stage, performance status and elevated platelet counts. Conclusions: These results indicated that platelet counts as well as some clinical pathologic characteristics could be useful prognostic factors in patients with unresectable NSCLC.